Capital adequacy ratio and financial performance in Vietnamese people’s credit funds: The moderating role of board and management gender diversity - Hung, Pham Duy; Dung, Ngo Thuy; Anh, Pham Tuan (Edelweiss Applied Science and Technology, 2026)
This study investigates the determinants of operational efficiency within 904 Vietnamese People’s Credit Funds during the period from 2020 to 2024. Utilizing a robust panel dataset of 4,520 observations, the research employs Fixed Effects Models with Robust standard errors to analyze the nexus between capital adequacy and the return on assets. Empirical results reveal that a higher capital adequacy ratio significantly reduces asset efficiency, which validates the opportunity cost of safety hypothesis in the cooperative banking sector. Furthermore, the debt-to-equity ratio and organizational scale exert negative influences on performance due to heightened administrative burdens and rising oversight costs. Regarding governance, board-level gender diversity exhibits a weak negative correlation with asset returns, while management-level diversity remains statistically insignificant. Notably, the interaction between capital buffers and inflation demonstrates that macroeconomic volatility effectively amplifies the prudential burden of overcapitalization. The research establishes that institutional productivity is primarily driven by internal financial discipline and the optimization of capital reserves rather than by the gender composition of leadership tiers. These findings suggest that the State Bank of Vietnam should adopt a risk-based regulatory framework to prevent the accumulation of excessive idle resources that erode the sustainability of member-owned credit funds.